Adaptation of Copyright and Related Rights to the Digital Single Market for Europe - Tsakova, Violeta (Research Papers, 2017)
New technologies and the Internet have radically changed the creative content market. They have provided authors, intermediaries and consumers with new methods for its commercial and non-commercial use. The existing European legal framework of copyright and related rights has proven to be incompatible with the new realities and has held back the use of new possibilities offered by digital technologies.In response to this challenge, measures have been taken to modernize the legal framework that has been implemented in the development of new regulations for the protection of copyright and related rights in the European Union. The study includes the reasons for the creation of these rules, their nature, the mechanisms for their enforcement and the expected results.The analysis clearly draws forward proposed indisputable regulations as well as highly controversial and unacceptable ones for reasons of concern to the important interests of the subjects covered by the new rules. On this basis, questions arise about improving the legislative activity of the Union as well as preparing the responsible institutions in Bulgaria for carrying out the national legislation in the field of copyright and its related rights in accordance with the changes in the European framework.